The Challenge of Measuring UK Wealth Inequality in the 2000s - Gonzalez Alvaredo, Facundo (2016)
The concentration of personal wealth is now receiving a great deal of attention - after having been neglected for many years. One reason is the growing recognition that, in seeking explanations for rising income inequality, we need to look not only at wages and earned income but also at income from capital, particularly at the top of the distribution. In this paper, we use evidence from existing data sources to attempt to answer three questions: (i) What is the share of total personal wealth that is owned by the top 1 per cent, or the top 0.1 per cent? (ii) Is wealth much more unequally distributed than income? (iii) Is the concentration of wealth at the top increasing over time? The main conclusion of the paper is that the evidence about the UK concentration of wealth post-2000 is seriously incomplete and significant investment in a variety of sources is necessary if we are to provide satisfactory answers to the three questions.